Interactive online services for learning foreign languages - Nataliya V. Ageyenko; Alla A. Rybkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Modern educational standards implementation requires the development of new learning process strategies. Introduction of innovative methods and technologies in the educational process allows to increase the efficiency of students learning activity and to choose an individual trajectory in an open educational environment. The study substantiates the necessity of development linguacultural competence of higher school students in the process of learning a foreign language. The authors identify the basic principles and distinctive features of language training; analyze the system and approaches to form students’ foreign language communicative competence. The paper discusses the advantages of using online platforms of virtual museums for the purpose of the development of student’s linguistic-country competence in higher educational institutions. Broad educational potential of virtual museums as an innovative resource that complements the curriculum and expands the traditional learning system, offering students knowledge of culture in the context of various activities is taken into account. The research represents a brief description of the virtual museum application for classroom tours in the process of teaching students and the developed and tested model of the formation of linguistic-country competence.